Hemoterapia em caninos: análise e indicações de 2.736 casos - Dutra, Lara Seffrin (2019)
Transfusion therapy aims the transfer of blood or blood products from donor to receptor according to the needs of the last. The use of blood products in veterinary medicine has been increasing in the last years, although more studies and spread of the knowledge regarding hemotherapy is needed. From fresh or stored whole blood (FWB, SWB), it is possible to obtain platelet-rich plasma (PRP), red blood cell concentrate (RBCC), platelet concentrate (PC), fresh, fresh frozen plasma or frozen plasma (P, FFP, FP) and cryoprecipitate (CRYO). The purpose of this study was to identify from the clinical and surgical routine of the Veterinary Teaching Hospital of the Federal University of Santa Maria (VTU-UFSM), canine patients whose clinical condition indicated the need of hemotherapy and to select the appropriate blood product. For that, 9,718 clinical records from the period of January 2015 to July 2018 and, based on clinical and laboratory parameters, 2,736 patients (32,53%) were identified as possible receptors. Of those, 1,692 (61,83%) were only anemic, 766 (28%) anemia and thrombocytopenia and 278, only thrombocytopenia. Indicated hemotherapy for each case were: 1,017 WB; 1,278 RBCC, 278 PRP or PC; 103 P, FP or FF, and in one case, CRYO. Associated clinical conditions related to the need of hemotherapy were: RBCC – secondary to cancer (28%), trauma (15%); WB – trauma (45%), viral infections (15%), hemoparasites (11%), PRC or PC – bone marrow depression associated to chemotherapy (26%), hemoparasites (23%), FP or FFP – viral infections (32%); CRYO – Von Willebrand disease, one case. The need of each blood product is variable depending to the studied regions and to the characteristics of the service. Reference centres for cancer should be prepared to offer a good blood bank service, as well as orthopaedic centres. Hemotherapy is a developing field in veterinary medicine and specific products are needed for particular clinical conditions, what reinforces the importance of a blood processing and storage service in order to offer the most indicated product for each patients need.